Molecular Typing and Variations in Amount of tst Gene Expression of TSST-1-Producing Clinical Staphylococcus aureus Isolates - Zhao, Huanqiang; Xu, Su; Yang, Han; He, Chunyan; Xu, Xiaogang; Hu, Fupin; Shu, Wen; Gong, Fang; Zhang, Chuanling; Liu, Qingzhong (Frontiers in Microbiology, 2019)
The toxic shock syndrome toxin-1 (TSST-1), encoded by tst gene, has been proposed to cause staphylococcal toxic shock syndrome (TSS) in a susceptible host, which highlights the need to evaluate the level of tst gene expression and molecular genetic characteristics of the tst-positive isolates. A total of 916 S. aureus isolates collected from seven hospitals in China were screened for the tst gene. The tst positive isolates were characterized by spa, SCCmec, PFGE and agr typing. Representative strains were also subjected to MLST typing. qRT-PCR was used to quantify tst and major virulence regulator genes expression. We also sequenced the regions of promoter and open reading frame (ORF) of tst to investigate whether they correlate with the variation in tst expression. We found 208 (22.7%) of surveyed isolates including 198 (29.8%) of MRSA and 10 (4.0%) of MSSA isolates harbored the tst gene. The most common clone among tst positive MRSA isolates belonged to ST5 (CC5)-agr2-t002-SCCmecII. The amount of tst mRNA varied 8.4 folds among clinical S. aureus isolates. Sequencing the tst promoter revealed a base T deletion in tst high expressed isolates. As for major virulence regulators, srrA, sarT, RNAIII and ccpA in four tst differentially expressed strains were detected to be highly expressed, respectively. Our study revealed high prevalence of ST5 (CC5)-agr2-t002-SCCmecII clone among tst positive MRSA in hospitals from China. The levels of tst expression among clinical S. aureus isolates varied, which may be associated with tst promoter and variations in specific virulence regulators.